2019
DOI: 10.1038/s41598-019-40414-y
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning approach to automatic teeth detection and numbering based on object detection in dental periapical films

Abstract: We propose using faster regions with convolutional neural network features (faster R-CNN) in the TensorFlow tool package to detect and number teeth in dental periapical films. To improve detection precisions, we propose three post-processing techniques to supplement the baseline faster R-CNN according to certain prior domain knowledge. First, a filtering algorithm is constructed to delete overlapping boxes detected by faster R-CNN associated with the same tooth. Next, a neural network model is implemented to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
159
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 25 publications
2
159
0
2
Order By: Relevance
“…To demonstrate the system’s robust performance, the algorithms were compared to the responses of three dentists, who reviewed the data set independently. Chen et al () concluded the AI machines performed at a success rate close to that of a junior dentist.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To demonstrate the system’s robust performance, the algorithms were compared to the responses of three dentists, who reviewed the data set independently. Chen et al () concluded the AI machines performed at a success rate close to that of a junior dentist.…”
Section: Discussionmentioning
confidence: 95%
“…Their results demonstrated that AI deep learning algorithms have potential for practical application within a clinical setting (Tuzoff et al ). Chen et al () presented a study to detect and number teeth in dental periapical films using faster regions with convolutional neural network features (faster R‐CNN) in the TensorFlow library. They used three post‐processing methods to integrate the basis of faster R‐CNN to improve detection predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faster regions with convolutional neural network features (faster R-CNN) in the TensorFlow tool package were used by Chen et al to detect and number the teeth in dental periapical films [16]. Here, 800 images were employed as the training dataset, 200 as the test dataset and 250 as the validation dataset.…”
Section: Tooth Detectionmentioning
confidence: 99%
“…There are several image techniques in the dentistry field depending on their use. Periapical images are employed to capture intact teeth, including front and posterior, as well as their surrounding bone; therefore, periapical images are very helpful to visualize the potential caries, periodontal bone loss and periapical diseases [16]. Bitewing images can only visualize the crowns of posterior teeth with simple layouts and considerably less overlaps [17].…”
Section: Introductionmentioning
confidence: 99%